Numerical investigation of Dean vortex evolution in turbulent flow through 90° pipe bends - Dutta, Prasun; Rajendran, Naveen Kumar; Cep, Robert; Kumar, Rakesh; Kumar, Himanshu; Nirsanametla, Yadaiah (Frontiers in Mechanical Engineering, 2025)
The current study focuses on numerically simulating turbulent flow in a 90° pipe bend using the k-ε turbulence model. Following validation of present numerical approach against prior experimental findings, extensive research was conducted to elucidate the development of Dean vortices and the secondary flow within the pipe bend. This study illustrated the distribution of mean axial velocity, secondary flow phenomena, and the occurrence of Dean vortices in various sections. Velocity vector distributions vividly depict the secondary motion induced by fluid transitioning from the inner to the outer wall of the bend, leading to flow separation. The interplay between the centrifugal force from the bend and adverse pressure gradient results in the formation of two counter-rotating vortices in the streamwise direction. This study presents numerical results aimed at providing insights into the behaviour of Dean vortices and the formation of secondary flow in a 90° pipe bend.